Adult Learning in Social Innovation - Cheryl K Baldwin; Rachel Lander (Adult Education Research Conference, 2017)
A qualitative study of practitioner learning in a multi-year, cross-sector, social innovation project indicated that team-based learning associated with the collaborative program model was expansive in character and influenced organizational learning beyond the project.
Keywords: social innovation; expansive learning; transformative learning